2018
DOI: 10.3892/mmr.2018.9471
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of xenoantigen‑stimulated T cell receptor Vβ‑restricted human regulatory T cells prevents porcine islet xenograft rejection in humanized mice

Abstract: Polyclonal expansion of human regulatory T cells (Tregs) prevents xenogeneic rejection by suppressing effector T cell responses in vitro and in vivo. However, a major limitation to using polyclonally expanded Tregs is that they may cause pan-immunosuppressive effects. The present study was conducted to compare the ability of ex vivo expanded human xenoantigen-stimulated Tregs (Xeno-Treg) and polyclonal Tregs (Poly-Treg) to protect islet xenografts from rejection in NOD-SCID interleukin (IL)-2 receptor (IL2r)γ−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Human CD4 Tregs exposed to pig xenoantigens have been shown to display xenospecific suppressive activity in vitro and in some studies these cells prolonged graft survival once they were transferred to an in vivo model 43 . Furthermore, baboon or human CD4 Tregs exposed to pig xenoantigens prior to adoptive transfer prolonged graft survival and suppressed T-cell responses 44,45 . Moreover, tolerance to nonsequestered meiotic germ cell antigens in the testis is CD4 Treg dependent 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Human CD4 Tregs exposed to pig xenoantigens have been shown to display xenospecific suppressive activity in vitro and in some studies these cells prolonged graft survival once they were transferred to an in vivo model 43 . Furthermore, baboon or human CD4 Tregs exposed to pig xenoantigens prior to adoptive transfer prolonged graft survival and suppressed T-cell responses 44,45 . Moreover, tolerance to nonsequestered meiotic germ cell antigens in the testis is CD4 Treg dependent 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In mice reconstituted with Xeno-or Poly-Treg and PBMC at a ratio of 1:10, it was found that over 75% of NICC xenografts survived over 84 days in the Xeno-Treg group vs 48 days in the Poly-Treg group, suggesting Xeno-Tregs may have greater ability to suppress xenogeneic cellular rejection. 38 In NHP, our group has reported that polyclonal Tregs administered at the time of GalTKO/hCD47Tg stem cells prolong the duration of donor chimerism. In these animals, we tested the potential for tolerance development by transplanting donor or donor-matched skin grafts without any maintained immunosuppression.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…A delayed allogenic kidney transplant was tolerated for over 290 days without immunosuppression in one of these animals, compared to a maximum of 4 weeks in those receiving BMT alone, suggesting that Tregs play a role in promoting chimerism and immunomodulation of allogeneic responses. 37 Recently, Jin et al 38 studied ex-vivo human Tregs expanded with xenoantigen stimulation (Xeno-Treg) and their effect on porcine neonatal islet cell clusters (NICC) in NOD-SCID IL-2rγ−/− mice. After adoptive transfer of human PBMC and infusion of ex-vivo expanded Xeno-Tregs or polyclonal Tregs (Poly-Tregs), NICC engraftment and survival was determined.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…This was supported by data showing enhanced in vitro suppression of human-anti-pig T cell responses by human CD4 + CD25 +high CD127 - Tregs that were expanded in vitro in the presence of pig peripheral blood mononuclear cells (PBMCs) combined with IL-2/Rapamycin and anti-CD3/CD28 magnetic bead stimulation ( 113 , 114 ). These enhanced human-anti-pig ( 112 , 115 ) or baboon-anti-pig Tregs proved effective in prevention of islet xenograft rejection in humanized or baboonized mouse models ( 114 ).…”
Section: The Role Of Regulatory T Cells In T Cell Mediated Islet Xeno...mentioning
confidence: 99%